An empirical assessment of business cycle asymmetries using parametric and non-parametric test: evidence from Asean countries - Abdul Manap, Turkhan Ali (2011)
Asymmetry is a key feature to understand the different behavior of expansions and recessions, and it provides a stylized fact that business cycle models should help to explain. Furthermore, the types of asymmetries provide guidance about underlying economic mechanism. This paper intends to adopt Clements and Krolzig (2003) parametric tests to determine the asymmetric properties of business cycle fluctuations of selected ASEAN countries for the period from 1978Q1 to 2009Q4. In particular, we model the business cycles of ASEAN Countries with the help of Markov Switching models and then apply the parametric tests of Clements and Krolzig (2003) to test for three types of asymmetry of business cycle: steepness, deepness and sharpness. This paper also uses three different approaches to remove trend component of GDP to investigate the sensitivity of the findings of asymmetries to the method of trend eliminations. Finally, for comparison, the non-parametric test of Randles et al. (1980) also will be employed. These findings have important implications for econometric modeling and policy making.